Pesticide thiram exposure alters the gut microbial diversity of chickens - Zhiwen Wu; Rongsheng Su (Frontiers in Microbiology, 2022)
Thiram is a major dithiocarbamate pesticide commonly found in polluted field crops, feed, and rivers. Environmental thiram exposure has been demonstrated to cause angiogenesis and osteogenesis disorders in chickens, but information regarding thiram influences on gut microbiota, apoptosis, and autophagy in chickens has been insufficient. Here, we explored the effect of thiram exposure on gut microbiota, apoptosis, and autophagy of chickens. Results demonstrated that thiram exposure impaired the morphology and structure of intestinal and liver tissues. Moreover, thiram exposure also triggered liver apoptosis and autophagy. The gut microbiota in chickens exposed to thiram exhibited a significant decline in alpha diversity, accompanied by significant shifts in taxonomic compositions. Bacterial taxonomic analysis indicated that thiram exposure causes a significant reduction in the levels of eight genera, as well as a significant increase in the levels of two phyla and 10 genera. Among decreased bacterial genera, seven genera even cannot be observed in the thiram-induced chickens. In summary, this study demonstrated that thiram exposure not only dramatically altered the gut microbial diversity and composition but also induced liver apoptosis and autophagy in chickens. Importantly, this study also conveyed a key message that the dysbiosis of gut microbiota may be one of the major pathways for thiram to exert its toxic effects.